Functional Outcome of Primary Repair of Long Flexors of Finger at Zone V with Early Mobilization - Hossain, Mohammad Sazzad; Faruquee, Sajedur Reza; Jahangir, Alom Md; Hamid, Md Zakaria Bin; Salam, Md Abdus; Hoque, Md Raihanul; Mahabubuzzaman, Mohammad (Community Based Medical Journal, 2024)
A prospective, observational study was conducted in National Institute of Traumatology and Orthopaedic Rehabilitation (NITOR), Dhaka, Bangladesh, between September 2019 and March 2021, to observe the functional outcome of primary repair of long flexors of finger at zone V with early mobilization. Our study included 51 patients, who had follow-up visits up to 12 months after operation. Tendon functionality was assessed by Buck-Gramcko score, while grip strength was assessed by modified sphygmomanometer. The mean age was 30.08±13.38 years. Middle and index fingers were most involved with both flexor digitorum superficialis (FDS) and flexor digitorum profundus (FDP) injury. In this study, most of the patients had excellent or good outcomes. The average return to work time was 32.82 weeks. 9.8% of the patients developed post-operative complications like infections, adhesion, and rupture. Most of the patients obtained good to excellent results (90%), while 3.92% had fair and only 2% had poor outcome. Early motion of the fingers seems to improve outcome in these patients. However, worse outcomes were seen in patients with a greater number of damaged structures, especially in concomitant nerve injury. CBMJ 2024 January: vol. 13 no. 01 P: 83-88